A Case Study to Evaluate the Combined Effect of Shatavari Ghrita Tarpana and Eye Exercises in Pratama Patalagata Timira with Special Reference to Simple Myopia - Mohana Kumari; S M Pasha (RGUHS Journal of AYUSH Sciences, 2025)
Simple myopia commonly referred to as lsquonearsightednessrsquo is a prevalent refractive error affecting millions worldwide. Signs and symptoms of simple myopia can be equated with the Lakshanas of Prathama Patalagata Timira. It is one among the Drishtigata netra rogas. Avyakta darshana impairment in vision is the main Lakshana mentioned under Prathama Patalagata Timira. Simple myopia is the most common refractive error seen in young children and adults. This case study delves into the management of simple myopia in a 21-year-old individual presenting with blurred distant vision. The subject visited Shalakya Tantra OPD at Government Ayurveda Medical College Bengaluru with Lakshanas of Pratama Patalagata Timira. The patient was thoroughly examined systematically reviewed and managed with Tarpana with Shatavari Ghrita and eye exercises. The patient showed considerable improvement subjectively and objectively. Improvement in visual acuity and autorefraction was observed in both the eyes. Simple myopia is a common refractive error with significant implications for daily functioning and overall quality of life. In this study combined use of Tarpana with Shatavari Ghrita and eye exercises demonstrated significant improvement in simple myopia.